2019
DOI: 10.5194/acp-19-7691-2019
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of rate coefficients and branching ratios for reactions of organic peroxy radicals for use in automated mechanism construction

Abstract: Organic peroxy radicals (RO 2 ), formed from the degradation of hydrocarbons and other volatile organic compounds (VOCs), play a key role in tropospheric oxidation mechanisms. Several competing reactions may be available for a given RO 2 radical, the relative rates of which depend on both the structure of RO 2 and the ambient conditions. Published kinetics and branching ratio data are reviewed for the bimolecular reactions of RO 2 with NO, NO 2 , NO 3 , OH and HO 2 ; and for their self-reactions and cross-reac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
202
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(212 citation statements)
references
References 160 publications
9
202
1
Order By: Relevance
“…As NO concentrations exceed 1ppb the first-generation RO 2 is scavenged by NO, thereby reducing the concentration of organonitrate HOM (Ehn et al, 2014), possibly affecting SOA yields. The MCM contribution also decreases with increasing NO concentra-tions mostly due to the formation of more volatile organonitrates (Jenkin et al, 2019).…”
Section: No X Dependencementioning
confidence: 97%
“…As NO concentrations exceed 1ppb the first-generation RO 2 is scavenged by NO, thereby reducing the concentration of organonitrate HOM (Ehn et al, 2014), possibly affecting SOA yields. The MCM contribution also decreases with increasing NO concentra-tions mostly due to the formation of more volatile organonitrates (Jenkin et al, 2019).…”
Section: No X Dependencementioning
confidence: 97%
“…In addition, TNCARB26 (closed shell carbonyl species) and RCOOH25 (pinonic acid) arise from the reaction of Criegee intermediates with water. RN18AO2 goes on to react with standard peroxy radical reaction partners; 195 HO2 forming hydroperoxides; NO and NO3 forming alkoxy radicals; and the peroxy radical pool forming alkoxy radicals, carbonyls and alcohols, as described in (Jenkin et al, 2019a).…”
Section: Ozonolysismentioning
confidence: 99%
“…The first order rate constants for autoxidation can vary over several orders of magnitude (~10 -6 -10 2 s -1 ) depending on nearby functional groups (Bianchi et al, 2019, Crounse et al, 2013, Xu et al, 105 2018, Kurten et al, 2015. Autoxidation rates also exhibit a significant positive temperature dependence (Jenkin et al, 2019a, Bianchi et al, 2019 and HOM yield has been observed to be highly temperature dependent (Quéléver et al, 2019). Thus, the overall competitiveness of autoxidation is dependent on the background atmospheric composition and ambient temperature as well as the molecule undergoing oxidation.…”
mentioning
confidence: 99%
See 2 more Smart Citations